2009
DOI: 10.1530/rep-08-0496
|View full text |Cite
|
Sign up to set email alerts
|

Preterm and infection-driven preterm labor: the role of peroxisome proliferator-activated receptors and retinoid X receptor

Abstract: Approximately 8% of births are complicated by preterm delivery. To improve neonatal outcomes, a greater understanding of the mechanisms surrounding preterm parturition is required. Peroxisome proliferator-activated receptors (PPARs) have been implicated in the regulation of labor at term where they exhibit anti-inflammatory properties. Thus, we hypothesize that dysregulation of PPAR expression and activity may be associated with preterm labor and infection-associated preterm labor. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Placental PPARg is particularly notable because it has strong antiinflammatory properties, including inhibition of pro-inflammatory cytokine gene transcription (Lappas et al 2002). Previous studies assessing the expression of placental PPARs (collected following vaginal delivery) have indicated that preterm (w34 weeks of gestation) and term placentas have equivalent PPARA (PPARa) mRNA and protein levels; however, protein expression of PPARD (PPARd) and PPARG (PPARg) is significantly higher in preterm placentas compared with term placentas (Holdsworth-Carson et al 2009). However, DNA binding of all the PPAR isoforms did not differ between the preterm and term tissues (HoldsworthCarson et al 2009), suggesting an equal functional capacity of PPARs across late gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Placental PPARg is particularly notable because it has strong antiinflammatory properties, including inhibition of pro-inflammatory cytokine gene transcription (Lappas et al 2002). Previous studies assessing the expression of placental PPARs (collected following vaginal delivery) have indicated that preterm (w34 weeks of gestation) and term placentas have equivalent PPARA (PPARa) mRNA and protein levels; however, protein expression of PPARD (PPARd) and PPARG (PPARg) is significantly higher in preterm placentas compared with term placentas (Holdsworth-Carson et al 2009). However, DNA binding of all the PPAR isoforms did not differ between the preterm and term tissues (HoldsworthCarson et al 2009), suggesting an equal functional capacity of PPARs across late gestation.…”
Section: Discussionmentioning
confidence: 99%
“…1H and I) expression was significantly lower after spontaneous preterm labour. Western blotting could not be performed on foetal membranes from the chorioamnionitis group due to protein degradation (Holdsworth-Carson et al 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Studies about the expression of PPARs in gestational tissues in PTL are few. Holdsworth-Carson et al 27 have shown that PPARb protein expression in choriodecidua is higher in the PTL group than in the TL group, whereas the amount of PPARa and PPARg is not different between the PTL and TL groups. Consistently, we showed that the PPARb amount was higher in the PTL with CAM group than in the TL group, whereas its amount in the PTL without CAM group was not different with that in the TL group.…”
Section: Regulation Of Pgdh In Chorion By Pparsmentioning
confidence: 96%
“…A study by the same group found that the expression of PPARb and PPARg in the placenta and PPARb in fetal membranes increases in labor at preterm. 27 In contrast, Berry et al 21 reported that PPARa mRNA in choriodecidua declines with labor, whereas PPARg and PPARb mRNA remain unchanged with labor.…”
mentioning
confidence: 98%